The Correlation between Years of Work and Work Shifts with Job Stress in Call Center Agents in the Surabaya Customer Service Company - Clariza Vioito Sinaga; Ayu Nurjanah (Universitas Airlangga, 2022)
Introduction: A Surabaya customer service company provides 24-hour call center services by implementing a work shift system, even though not all employees can adjust to work shifts. New employees must perform some adjustment or adaptation to their job. They must remain calm and patient in providing information and solving problems that customers convey, resulting in a very high mental needs of each call center agent. Monotonous activity and unpleasant customers trigger work stress on employees, which is marked by complaints of dizziness after work and emotional feeling. The objectives of this study was to analyze the correlation between years of works and work shifts with job stress in call center agents of the Surabaya customer service company. Methods: This study was a descriptive observational study with a cross sectional study design. The population in this study was all call center agents of a customer service company in Surabaya. The samples were 45 respondents, obtained through random sampling. Data were obtained from answered questionnaires and were analyzed using the contingency coefficient test. Results: Most call center agents had years of work of ≥ 1-3 years (53.3%). They also experienced very heavy job stress (51.1%). The results of the contingency coefficient was 0.436. The majority of call center agents experienced very heavy job stress, specifically those working in the morning shift (53.3%), day shift (40%) and night shift (60%). The results of data analysis using the contingency coefficient test was 0.338. Conclusion: There was a moderate correlation between years of work and job stress. There was a low correlation between work shifts and job stress.Keywords: years of work, work shift, job stress